2013
DOI: 10.1097/dcr.0b013e318273a182
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of the Jinling Procedure for Combined Slow-Transit Constipation and Obstructive Defecation

Abstract: Our clinical practice demonstrates that Jinling procedure is safe and effective for refractory slow-transit constipation associated with obstructive defecation, with minimal major complications, significant improvement of quality of life, and a high satisfaction rate after 4-year follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
(40 reference statements)
0
29
0
Order By: Relevance
“…Slow transit constipation, which is one type of chronic idiopathic constipation, has an important pathophysiological feature of decreased colonic motility, which could be diagnosed by using radiopaque markers, as occurred in this study [28]. Recently, many researchers have focused on the relationship between intestinal microbiota and constipation and have demonstrated that intestinal microbiota contribute to the pathophysiology of functional gastrointestinal disorders [29].…”
Section: Discussionmentioning
confidence: 95%
“…Slow transit constipation, which is one type of chronic idiopathic constipation, has an important pathophysiological feature of decreased colonic motility, which could be diagnosed by using radiopaque markers, as occurred in this study [28]. Recently, many researchers have focused on the relationship between intestinal microbiota and constipation and have demonstrated that intestinal microbiota contribute to the pathophysiology of functional gastrointestinal disorders [29].…”
Section: Discussionmentioning
confidence: 95%
“…Surgery for constipation would normally be carried out on patients with the most refractory symptoms. In this review, 48 studies involving surgical treatment of constipation were included: 32 of which were surgical series, 6,[14][15][16]21,[26][27][28][29][30][32][33][34][35]37,39,41,43,45,46,48,49,[51][52][53][54]56,[58][59][60]63 while 16 were studies on colonic tissue obtained at colectomy. [8][9][10][11][17][18][19][20]22,23,25,31,36,44,62,66 Seven of the pathological series came from one center 10,11,…”
Section: (Continues)mentioning
confidence: 99%
“…[8][9][10][11][17][18][19][20]22,23,25,31,36,44,62,66 Seven of the pathological series came from one center 10,11,19,20,22,25,44 and three from another group. 23,31,36 The duration of constipation prior to inclusion ranged from at least 6 weeks 51 to 6 years 53,56,63 or a mean duration of 14.6 years 17 or 19 years. 18 A number of studies used Rome II 20,26,35,37,52,62 or Rome III 45,53,56 criteria for defining functional constipation, implying minimum symptom duration as 12 or 6 months, respectively.…”
Section: (Continues)mentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to a generalized gastrointestinal dysmotility, concomitant organic or functional pelvic floor disorders, and psychological problems [101,102]. This is a modified operation of subtotal colectomy with cecorectal anastomosis that is not end to end but side to side, with good results, minimal major complications, and significant improvement in the quality of life at 4-year follow-up [107]. Another operation for refractory slow transit constipation with obstructed defecation is the 'Jinling procedure' (Level of Evidence: Class III; Grade of Recommendation: C).…”
Section: Surgical Treatmentmentioning
confidence: 99%